Prevalence and determinants of sexual intimate partner violence against women in the city of marivan, iran. - Arezoo Yari; Roonama Nouri; Hamideh Rashidian; Haidar Nadrian (Tehran University of Medical Sciences, 2013)
Objective: The aim of this study was to estimate the prevalence of sexual intimate partner violence (SIPV) and to investigate its associated factors among women attending public obstetrics, genecology, and family planning health services of the city of Marivan, Iran. Materials and methods: This multistage cluster sampling study recruited 770 women attending the public obstetrics, gynecology and family planning health services of the city of Marivan from May to November, 2009. Results: Our findings confirmed that about one-third of the women experienced SIPV (32.9%). Statistically significant differences were found (p < .001) in SIPV by almost all demographic and characteristic variables. Woman's circumcision, forced marriage, spouse's infidelity, level of sexual desire, woman's pleasure from intercourse, and spouse's inattention to woman's sexual satisfaction during intercourse were statistically significant predictors of SIPV, and also, were accounted for 61.8% of the participants. Conclusion: Public health centers and health-care providers should focus on both women and their spouses in order to participate in both national and community level of educational and promotional intervention programs. Without their participation, the likelihood of success in decreasing SIPV against women would be low.